FREQUENCY OF IMMEDIATE POSTOPERATIVE COMPLICATIONS: CSF LEAK INCIDENCE IN PATIENTS UNDERGOING SURGERY FOR SPINAL DYSRAPHISM (Journal of Medical & Health Sciences Review, 2025)
Background: Cerebrospinal fluid (CSF) leakage is a substantial complication that results from spinal dysraphism surgery, which contributes to prolonged hospital stays and increased morbidity rate.Objectives: This investigation was carried out to ascertain the frequency of immediate postoperative CSF leakage, identify risk factors that are associated with these leaks and assess the clinical outcomes in patients who are undergoing spinal dysraphism surgery.Methods: From January to December 2023, 40 patients who underwent surgery for spinal dysraphism were included in this cross-sectional study. The analysis encompassed postoperative outcomes, clinical characteristics, surgical details and patient demographics. Focusing on factors such as intraoperative complications, surgical complexity and tethered cord syndrome, statistical comparisons were conducted between patients with and without CSF leakage.Results: Six patients (15%) experienced CSF leaks, with statistically significant association observed in those with tethered cord syndrome (66.7 vs. 23.5%, p